Morphofunctional Alterations in Peribronchial Lymph Nodes of COVID-19-Related Deaths: A Comparative Study - Aibek Turganbaev, Mukambet Mukashev, Nagasree Golla, Tugolbai Tagaev (Asian Journal of Pharmaceutics (AJP), 2025)
Background: The coronavirus disease-19 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2, has significantly impacted people worldwide. Reverse transcription polymerase chain reaction is the primary method for validating COVID-19 cases; however, its sensitivity is limited. The lymphatic system, which plays a crucial role in maintaining homeostasis, is also affected by pathological conditions. COVID-19 is characterized by endotheliitis, which involves the blood vessels in the lungs. This study aimed to investigate morpho-functional changes in the peribronchial lymph nodes in COVID-19-related deaths. Materials and Methods: This study established methods and specialized techniques for forensic materials and analyzed the lymph nodes of 45 COVID-19 deceased individuals. Cutting 5–6 μm slices using a rotary microtome, the samples were stained with hematoxylin and eosin for general histological examination. Results: This study found significant structural changes in the lymph nodes, including a disrupted structure, lack of follicles, unevenly thickened and sometimes absent capsules, random arrangement of cellular elements without forming follicles or reproduction centers, prevalence of mature lymphocytes and a large number of macrophages, large cells, both young and mature plasma cells, frequent observation of large cells with two or three nuclei, and the presence of fibrin and fibrin-like deposits in blood vessels, erythrocytes, and fibrin blood clots in the parenchyma and stroma of the lymph nodes, as well as numerous sharply expanded cavities filled with lymph, resembling cysts, but without a capsule. Conclusion: This study suggests that these morphological changes may serve as additional criteria for confirming the cause of death due to COVID-19.